(untitled) (Vietnam Journal of Community Medicine, 2022)
The systematic review research analyzed the overall system by gathering documents from various sources from January 2010 to June 2022 to describe the accounting methods for the unit cost of curative services at health facilities and its application at the primary healthcare level. Unit cost analysis applied to medical facilities has been widely deployed in many countries around the world. The bottom-up cost analysis study provided more accurate results but was not widely applied. The combination of both top-down and bottom-up methods has been curently a solution to overcome the limitations of these methods. In Vietnam, unit cost analysis applied at primary health care was still limited in number of issues and mainly focus on setting of service prices and costs of diseases.